Influence of Throw-Catch and Catch-Only Training on Table Tennis Forehand Drive Accuracy - Iane Isnaeni Khayatul Wakhidah; Aziz Amrullah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to examine the effect of to throw-catch and catch-only training on the accuracy of the forehand drive strokes in table tennis athletes, as well as to compare the effectiveness of both training methods. This research employed a quantitative approach using a quasi-experimental design in the from of a two-group prestest-posttest design. The sample consisted of 16 table tennis athletes selected through purposive sampling. The instruments used in this study included a forehand drive accuracy test, a hand-eye coordination test (throw-catch), and a reaction test (catch-only). Data analysis techniques and independent sample t-test with a significance level of 0.05. the results showed an improvement in the accuracy of forehand drive strokes after the intervention in both groups. Statistical analysis revealed a significant difference between the effects of throw-catch and catch-only training (p < 0.05). furthermore, throw-catch training was found to be more effective in improving forehand drive accuracy compared to catch-only training.